تقييم الأداء الإنتـــــاجي لدجاج البيــــاض سلالة Hy-line تحت الظروف الليبية - الفوني , أنور ناجي عبد الله; الشلماني , محمد إدريس; سالم , ناصر خليفة محمد (Scientific Journal of University of Benghazi, 2023)
The study was carried out in a private sector farmspecializing on commercial egg production (Ali Shabaan’s farm), located five kilometresfrom northern Suluq. The study's objective was to investigate the productive performance of Hy-line layers under Libyan conditions. Records of three houses of white egg Hy-line layers were used from 13/5/2019 to 24/11/2020 under Libyan management, where some productive and livability traits were measured, including a percentage of daily hen day egg production (HDEP), hen house egg production (HHEP), daily egg production, accumulation mortality rate and feed efficiency (kg diet/12 eggs)The findings showed HDEP and HHEP at 31 week age was 95% and 93%, respectively. The number of egg production was 311 and 285 eggs/year in HDEP and HHEP, respectively. The accumulation mortality rate increased during the production phase to 16.7%, affecting layers' production efficiency. On the other hand, no significant differenceswere observed on feed efficiency, except during the first two weeks of the production phase, which fluctuated.